PENERAPAN MODEL COOPERATIVE LEARNING TIPE STUDENT TEAMACHIEVMENT DIVISION UNTUK MENINGKATKAN AKTIVTAS SISWA PADAPEMBELAJARAN MATEMATIKA (Penelitian Tindakan Kelas pada siswa kelas VB SDN 81 Kota Bengkulu) - sari, yolanda tirta; juarsa, osa (UNIB Press, 2017)
ABSTRACTThis research aims to analyze the increase in student activity in mathematics learning by applying cooperative learning model type STAD to VB grade students of SDN 81 Bengkulu City, and to describe the application of the right STAD type cooperative learning model so as to increase student activity in mathematics learning. The subjects of this study amounted to 29 people. Data collection techniques use observation and documentation techniques. The data collected in this study is the observation data of increasing student activity and data on the implementation of STAD type cooperative learning model in mathematics learning. Data analysis techniques used qualitative descriptive analysis. The results of this study indicate an increase in student activity in learning mathematics in class VB SD Negeri 81 Kota Bengkulu. This is evidenced by the activities of students in learning mathematics has increased in cycle II. In cycle 1 only a small number of students were active in learning and there were still some aspects of student activity that had not yet appeared in the core activities of interpretation and activity evaluating activities, while in cycle II the success indicators had been fulfilled, namely most students carried outPenerapan Model Cooperative Learning Tipe Student Team Achievent Divisionlearning activities or more than ½ (half) the number of students, more than 15 students carrying out learning activities on: opening, core and closing activities very well. The application of the STAD learning model is appropriate to increase student activity in mathematics learning, namely by providing motivation and guidance so that students can actively explore in groups as well as appreciation in the form of rewards. Thus, the application of the appropriate STAD learning model can increase students' activities in the mathematics learning of VB grade students of SD Negeri 81 Kota Bengkulu.Keywords: Student Achievement Team Division, Student Activity, Mathematics Learning.